Topkapı Sarayı Müzesindeki saatların kataloğu = Catalogue of clocks and watches in the Topkapı Sarayı Museum = Katalog der ausgestellten uhren im Topkapı Sarayı Museum zu Istanbul = Catalogue des pendules et montres exposées au Musée de Topkapı Sarayı à Istanbul. - Meyer, Wolfgang. (İstanbul)
yak. 100 s.